PHYSICOCHEMICAL FOUNDATIONS OF THE FORMATION OF SILICON–METAL COMPOSITE THERMOELECTRIC MATERIALS - Mamirov Abduvoxid Muxammadamin ugli (Ethiopian International Journal of Multidisciplinary Research, 2026)
This study presents a comprehensive investigation of the physicochemical mechanisms and technological features involved in the formation of silicon-based metal composite materials. Alkali metal atoms were introduced into the silicon crystal lattice using a contact method based on the incorporation of metallic particles, and their interaction with the lattice structure was analyzed in detail. In the subsequent stage, thermal treatment processes were carried out to examine the formation mechanisms of composite phases, diffusion behavior, and structural reorganization phenomena. The obtained results demonstrate that the spatial distribution of metal atoms, microstructural evolution, and morphological changes significantly influence the thermoelectric and electrical conductivity properties of the material. In addition, it was established that the optimization of doping levels and thermal treatment parameters plays a crucial role in controlling the material properties. The findings of this research provide an important scientific basis for the development of high-performance silicon-based thermoelectric composite materials, expanding their functional capabilities and enhancing their potential for practical applications.